The extensive cultivation of Pyropia haitanensis along the coastal areas influences the ecological dynamics of nearby intertidal mudflat pond water - Peihao Liu; Qijun Luo; Shanshan Zhu; Juanjuan Chen; Rui Yang; Tingting Niu; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science)
IntroductionThe aquaculture in intertidal mudflat ponds on the coast of the East China Sea typically coexists with oceanic seaweed cultivation in the nearby open water area, forming an interconnected aquatic ecosystem. This study aimed to understand the impact of the seaweed cultivation on the water quality and microbial communities in their neighboring intertidal mudflat ponds.MethodsA unique recirculating culture system was established, integrating seaweed farming in marine areas with aquaculture ponds on mudflats, and incorporating an effluent treatment process for added efficiency. Water samples were collected from three sites, including open water areas with or without seaweed (Pyropia haitanensis) cultivation, the aquaculture mudflat ponds, and effluent water ponds, with control sites for comparison. The dynamic diversity patterns and structure of microbial communities were determined by 16S and 18S rRNA sequencing, and the environmental factors were measured.ResultsIn the offshore aquaculture area, the cultivation of P. haitanensis increased the dissolved oxygen and pH, decreased inorganic nutrients, reduced the alpha diversity of bacteria, established the dominance of Proteobacteria, but did not influence the composition of microeukaryotes. These changes in the seawater subsequently affected the dynamics in the corresponding aquaculture ponds, where the water quality was improved, the microbial diversity was enhanced, and the abundance of functional bacteria such as Microbacteriaceae was increased. According to the co-occurrence network analysis, the cultivation of P. haitanensis potentially improved the stability of the microbial communities in both the offshore aquaculture area and the onshore aquaculture ponds and allowed them to resist stress better. In addition, after the effluent from the aquaculture ponds was purified in the treatment ponds with mangroves and oysters, the water quality improved and the abundances of Dinophyceae and Bacillariophyta decreased.DiscussionThis study highlights the positive effects of P. haitanensis cultivation on water quality and microbial stability in adjacent aquaculture ponds.